Isokinetic muscle strength asymmetry and imbalance in the lower limbs of professional soccer players - Fousekis, K.; Tsepis, E.; Vagenas, G. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Background. Nearly every soccer player possesses some degree of functional footedness, which results to consistent asymmetrical workloads and neuromuscular adaptations in its lower limbs. This gradually induces a potential impact to the mechanisms of injury, which also involve agonist-antagonist muscle strength imbalance during knee function. Previous data on muscle strength asymmetry in athletes are supportive of this idea (Tsepis et al. 2004; Markou & Vagenas, 2006). Additionally, physical demands vary according to the playing position in the field. Purpose. The purpose of the study was to investigate dominance related strength asymmetry of the knee extensors and flexors in soccer players. Muscle imbalances between agonist-antagonist groups were also analyzed and playing positions were compared. Methods. 37 professional soccer players (age 21.5 ± 4.5 yrs, height 183 ± 8.4 cm, body mass 72.5 ± 6.9 Kg) were selected by their clear footedness (23 Right-footed & 14 left-footed). Their lower limbs were subjected to isokinetic knee extension and flexion testing concentrically, at 60o, 180o and 300o/sec, and eccentrically, at 60o and 180o/sec, using a Cybex II dynamometer. Muscle strength was quantified by maximal peak torque (PT) of the knee extensors and flexors and by the conventional (con/con & ecc/ecc for extension - flexion) and functional (antagonist ecc / agonist con and antagonist con / agonist ecc) flexor/extensor strength ratio. Results. A highly significant asymmetry between the dominant and the non-dominant lower extremity was found at the 60o/sec angular speed for concentric and eccentric knee extension, and for eccentric knee flexion (p<0.01). No differences were found in the rest of comparisons regarding the faster angular velocities and the ratios (p>0.05). Grouping of players according to their field position (defenders, midfielders and attackers) did not reveal any significant differences (p>0.05). Conclusions. Soccer players with profound footedness possess significant lateral footedness-dependent muscle strength asymmetry under low angular velocity conditions. During the game, maximal strength and power movements are accumulated with higher sifts of myo-dynamic demands to the dominant side. The higher isokinetic velocities may not be involved to the usual dynamic patterns to that extend as to impose clearcut strength asymmetry in the limbs. The conventional and functional ratios, being normalized indices of the isokinetic profile, do not seem to associate to muscle strength asymmetry. A uniform strength profile characterizes players of different field positions in soccer.